AB0008 Type I Interferon Gene Response is Associated with Early Rheumatoid Arthritis (RA). (9th June 2015) - Enciso-Moreno, J.A.; Castañeda-Delgado, J.E.; Macias-Segura, N.; Santiago-Algarra, D.; Castillo-Ortiz, J.D.; Alemán-Navarro, A.L.; Martínez-Tejada, P.; García-De Lira, Y.; Olgín-Calderόn, D.; Enciso-Moreno, L.; Bastián-Hernández, Y.; Ramos-Remus, C.R.
Abstract : Background: Rheumatoid arthritis (RA) is often accompanied by severe inflammation joint destruction and circulating autoantibodies. Recently it as been described that inflammatory responses associated with type I interferon are associated with the disease, however, there is no information regarding the role of the response of these associated gene signatures with other stages of the disease such as early RA or individuals at risk such as those with anticitrullinated antibodies and direct and family history of RA. Objectives: To evaluate the relative gene expression of the genes IFI44L, IFI6, IFIT1, IFIT2, IFI35, ISG15, MXB, MXA, Ly6E, RSAD2, HERC5, EPSTRI1 in blood samples isolated from patients with RA and their family members with preclinical stages of the disease. Methods: Blood samples from Mexican patients with early RA (eRA; n=10) and patients with chronic RA with more than 2 years with the disease (cRA; n=20) were collected. All cRA patients had received treatment with DMARD's. First-degree relatives of patients with RA were stratified in positive (ACCP+; n=20) or negative (ACCP-; n=20) to ACCP. Subjects without family history of autoimmune diseases were included in a healthy control group (HC; n=20). Serum levels of ACCP were evaluated using second generation ELISA. RNA was isolated and integrity was verified in a Bioanalyzer (Life Technologies), only samples with RIN scores>6 were used for cDNA synthesis by a superscript II reverse transcription system (Invitrogen), according to manufacturers instructions.qPCR analysis of the samples was carried out in a Lightcycler 480 (Roche diagnostics) and normalized using HPRT. Statistical analysis for group comparison was done using the Kruskal-Wallis test for non-parametric data, with p<0.05 considered significant. A spearman correlation was also performed. Results: No differences were found for clinically relevant variables (HC, ACCP-, ACCP+, eRA and cRA). Differences between the chronic arthritis group and the healthy controls were identified for IFIT1, IFIT2, IFI35, ISG15, Ly6E, HERC5, RSAD2, EPSTRI1 and MXA (p<0.05) confirming previous reports in our population. However, differences among the healthy controls or the ACPA- individuals and the eRA cases were also identified for the genes IFI 5, MXA and MXB (P<0.05). A significant correlation was found for several genes in the signalling cascade such as IFIT1, EPSTRI1, IFI35, LY6E, HERC5 and MXA (P<0.05) suggesting that once that the cascade has been initiated, al genes belonging to the cascade are expressed to regulate the type I interferon gene response. Conclusions: The gene expression signature of the type IFN response is overexpressed in the majority of the genes analysed, however, several of these genes are also overexpressed in the early RA subjects, suggesting that the expression of these genes might be used as an early detection system for patients with early disease symptoms. The use of the markers to further advance the classification of undifferentiated arthralgia and early RA needs to be further explored. Disclosure of Interest: None declared